ASC Timetables for Setting Subjects in Integrated Islamic Elementary School; Intelligent Planning for Learning Systems - Yahya; Wahyu Fitrina Defi; Weli Febrina (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study investigates the implementation and effectiveness of ASC Timetables, an intelligent planning system, in setting subjects for an Integrated Islamic Elementary School at Riyadhoturrohman Panyabungan. The research explores the complexities of scheduling subjects within the context of Islamic education and analyzes the intelligent planning mechanisms integrated into ASC Timetables. A qualitative research approach, employing in-depth interviews, observations, and document analysis, was utilized to gather data from teachers, school administrators, and staff directly involved in using ASC Timetables.The findings of this study reveal the intricate process of subject scheduling in an integrated Islamic elementary school and highlight the significance of intelligent planning systems in managing diverse subjects while adhering to Islamic educational principles. The research illuminates the challenges faced by educators and administrators and discusses the solutions provided by ASC Timetables. Moreover, it identifies the system’s ability to adapt and optimize schedules, ensuring an effective and balanced allocation of learning hours for various subjects. This research contributes to the understanding of how intelligent planning systems like ASC Timetables enhance the efficiency of subject scheduling in a unique educational context. The insights gained from this study can inform educational practitioners, policymakers, and system developers, guiding the integration of intelligent planning tools in diverse educational environments, especially those with specific cultural and religious requirements.